Management of severe trauma worldwide: implementation of trauma systems in emerging countries: China, Russia and South Africa - (:unkn) unknown (My University, 2021)
As emerging countries, China, Russia, and South Africa are establishing and/or improving their trauma systems. China has recently established a trauma system named "the Chinese Regional Trauma Care System" and covered over 200 million populations. It includes paramedic-staffed pre-hospital care, in-hospital care in certified trauma centers, trauma registry, quality assurance, continuous improvement and ongoing coverage of the entire Chinese territory. The Russian trauma system was formed in the first decade of the twenty-first century. Pre-hospital care is regionbased, with a regional coordination center that determines which team will go to the scene and the nearest hospital where the victim should be transported. Physician-staffed ambulances are organized according to three levels of trauma severity corresponding to three levels of trauma centers where in-hospital care is managed by a trauma team. No national trauma registry exists in Russia. Improvements to the Russian trauma system have been scheduled. There is no unified trauma system in South Africa, and trauma care is organized by public and private emergency medical service in each province. During the pre-hospital care, paramedics provide basic or advanced life support services and transport the patients to the nearest hospital because of the limited number of trauma centers. In-hospital care is inclusive with a limited number of accredited trauma centers. In-hospital care is managed by emergency medicine with multidisciplinary care by the various specialties. There is no national trauma registry in South Africa. The South African trauma system is facing multiple challenges. An increase in financial support, training for primary emergency trauma care, and coordination of private sector, need to be planned.
Keywords: African Research